2010
DOI: 10.1097/sle.0b013e3181d823df
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the Therapeutic Effect of Hepatectomy Versus Radiofrequency Ablation for the Treatment of Hepatocellular Carcinoma

Abstract: Surgical resection has been considered to be the best treatment for hepatocellular carcinoma (HCC). However, in recent years, there has been growing interest in the therapy of radiofrequency ablation (RFA). This meta-analysis is to evaluate the therapeutic effect of those 2 therapeutic methods. Outcomes evaluated were death rate, complications, survival rates, recurrence-free survival rates, and recurrence. Primary authors were contacted to retrieve further information if necessary. There is no significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…Head-to-head comparisons between RFA and resection have been conflicting, with one randomized trial [20] demonstrating essentially no difference in overall survival (OS), and the other [9] indicating improved results for surgery over RFA. Similar conflicts are found in two meta-analyses, with one [21] showing equivalent survival rates despite higher rates of local recurrence with RFA, and the other [22] demonstrating better survival rates in surgical patients with tumor sizes ≥3 cm in diameter and equivalent rates in smaller tumors.…”
Section: Local Ablative Therapymentioning
confidence: 63%
“…Head-to-head comparisons between RFA and resection have been conflicting, with one randomized trial [20] demonstrating essentially no difference in overall survival (OS), and the other [9] indicating improved results for surgery over RFA. Similar conflicts are found in two meta-analyses, with one [21] showing equivalent survival rates despite higher rates of local recurrence with RFA, and the other [22] demonstrating better survival rates in surgical patients with tumor sizes ≥3 cm in diameter and equivalent rates in smaller tumors.…”
Section: Local Ablative Therapymentioning
confidence: 63%
“…Eighteen meta-analyses compared the outcomes of RFA versus surgical resection [11, 16, 24, 27, 31, 33, 47, 61, 69, 72, 89, 97, 106, 117, 119, 127, 151, 153]. As for the OS, seven of them favored surgical resection [27, 31, 47, 61, 97, 106, 127]; four demonstrated that the OS was statistically similar between the two groups [11, 16, 119, 151]; four showed that the 1-year survival was statistically similar between the two groups, but the 5-year survival was better in surgical resection group [33, 72, 89, 117]; one found that the 1- and 5-year survival were statistically similar between the two groups, but the 3-year survival was better in surgical resection group [155]; one reported that surgical resection had better OS than RFA in the subgroup analyses of a single nodule 3–5 cm and ≤ 3 cm, but the OS was statistically similar between the two groups in the subgroup analyses of a single nodule < 2 cm and 2–3 nodules < 3 cm [24].…”
Section: Ablation Therapymentioning
confidence: 99%
“…As for the DFS, nine of them favored surgical resection in terms of DFS/RFS at any time points [11, 27, 31, 61, 72, 89, 97, 106, 155]; three showed that the 1-year DFS was statistically similar between the two groups, but the 3- and/or 5-year DFS were better in surgical resection group than in RFA group [16, 33, 151]; one reported that surgical resection had better DFS than RFA in the subgroup analyses of a single nodule 3–5 cm and ≤ 3 cm, but the DFS was statistically similar between the two groups in the subgroup analyses of a single nodule < 2 cm and 2–3 nodules < 3 cm [24]. …”
Section: Ablation Therapymentioning
confidence: 99%
“…In Asia, hepatitis B virus infection is common; in the West and Japan, hepatitis C infection is the main risk factor, as well as alcohol [1]. Although liver transplantation and surgical resection remain the gold standard, only a small percentage of patients are good candidates for these modalities [3][4][5]. Recently there has been a paradigm shift in the treatment algorithm of patients with HCC, with radiofrequency ablation (RFA) being considered an alternative to resection for small HCC [3,[6][7][8][9].…”
mentioning
confidence: 99%